Seiberg-Witten for Spin(n) with spinors - Chacaltana, Oscar [UNESP] (2015)
N = 2 supersymmetric Spin(n) gauge theory admits hypermultiplets in spinor representations of the gauge group, compatible with beta <= 0, for n <= 14. The theories with beta < 0 can be obtained as mass-deformations of the beta = 0 theories, so it is of greatest interest to construct the beta = 0 theories. In previous works, we discussed the n <= 8 theories. Here, we turn to the 9 <= n <= 14 cases. By compactifying the D-N (2,0) theory on a 4-punctured sphere, we find Seiberg-Witten solutions to almost all of the remaining cases. There are five theories, however, which do not seem to admit a realization from six dimensions.